Wrinkling and Folding in Copper Single Crystals under Compression and Sliding - Lychagin D. V. Dmitry Vasilievich; Tarasov S. Yu. Sergei Yulievich; Chumaevskii A.; Alferova (Alfyorova) E. A. Ekaterina Aleksandrovna (Structure Materials, Mechanics and Dynamics of Materials, 2015)
Title screen